Die akademie in Suid-Afrika: ’n vervullende professie? - Walt, J. L. van der (Koers, 2009)
Academe in South Africa: a fulfilling profession? South African academics possess a collective value system. However, other value systems impact not only on their value system but also on their academic work. They typically find themselves working in an institutional, a national and an international context, each with its own hierarchy of values. A theoretical discussion of (the role of) values in the academic workplace is followed by an overview of the professional values held by South African academics as measured by means of the Changing Academic Profession (CAP) Survey, which was carried out in 2008. The survey revealed, for instance, a rift between the institutional value hierarchy and that of the academic profession. It can therefore be concluded that many South African academics seem to lead relatively unfulfilled professional lives, among others, because they find themselves working in an environment (various contexts) with many contradictions. These problems should be addressed for the sake of the well-being of both the academic profession and of the higher education sector.